A Simple, Small‐Bandgap Porphyrin‐Based Conjugated Polymer for Application in Organic Electronics. Issue 21 (10th September 2018) - Yang, Fan; Li, Cheng; Wei, Yuanzhi; Yan, Nanfu; Wang, Xiaohui; Liu, Feng; You, Shengyong; Wang, Jizheng; Ma, Wei; Li, Weiwei
Abstract: A simple, small‐bandgap porphyrin‐based conjugated polymer with ethylnyl linkers is prepared for application in organic electronics. Beneficial from quinoid resonance form, the polymer showed near‐infrared absorption up to 1000 nm and strong photoluminescence emission with a quantum yield of 0.2%. The polymer can be successfully applied to several electronic devices, such as organic field‐effect transistors with ambipolar charge transport, organic solar cells with a high external quantum efficiency of 0.58 at 970 nm, and organic photodetectors with high responsibility and detectivity. Abstract : A porphyrin‐based conjugated polymer with ethylnyl linkers is developed to perform small‐bandgap absorption up to 1000 nm and shows successful application in organic electronics devices.